Pelatihan Penerapan Pembuatan Buku Kas Pada Warung Bakaran Di Desa Giripurwo, Kec. Purwosari, Kabupaten Gunung Kidul, Daerah Istimewa Yogyakarta - Devi Choirunissa Abelia (Universitas Katolik Widya Karya Malang, 2023)
The MSME sector is a form of a developing economy based on the concept of people's economic development. Sufficient insight is needed in managing MSMEs because it influences the success of the business being carried out. Within the MSME category, there are various types of businesses, one of which is a burnt stall. Warung Bakaran is located in Giripurwo Village, Kec. Purwosari, Gunung Kidul Regency, Special Region of Yogyakarta. This activity was carried out to help apply accounting knowledge to the business owner of Warung Bakaran Ibu Tedjo. This activity is a field research using survey techniques, outreach and direct training in the field. The activity begins with the provision of material, practice and evaluation. The results obtained from this research, Ms. Tedjo, although she has somewhat less knowledge, is willing to learn, so that in providing material about the importance of making a cash book, she is relatively quick to understand. The results during practice were quite good because he quickly understood if there was an error in recording and was given understanding. With this, for now Warung Bakaran is neater in terms of recording sales and expenses.